Biomechanical risk factors and mechanisms of knee injury in golfers - Marshall, R. N.; McNair, P. J. (Sports Biomechanics, 2013)
Knee injuries in golf comprise approximately 8% of all injuries, and are considered to result from overuse, technical faults or a combination of those factors. This review examines factors involved in injury, including the structure of the knee joint, kinematics and kinetics of the golf swing, forces sustained by knee joint structures and the potential for joint injury as well as injury prevention strategies. The golf swing generates forces and torques which tend to cause internal or external rotation of the tibia on the femur, and these are resisted by the knee ligaments and menisci. Research has shown that both maximum muscle forces and the forces sustained during a golf swing are less than that required to cause damage to the ligaments. However, the complex motion of the golf swing, involving both substantial forces and ranges of rotational movement, demands good technique if the player is to avoid injuring their knee joint. Most knee injury in golf is likely related to joint laxity, previous injuries or arthritis, and such damage may be exacerbated by problems in technique or overuse. In addition to appropriate coaching, strategies to remedy discomfort include specific exercise programmes, external bracing, orthotics and equipment choices.